Sistem Penjamin Mutu Internal (SPMI) (dI UPTD SMP N 2 Kisaran) - Dyna Sibarani; Elfrianto Elfrianto; Feronika Rismaida; Bordaleni Siregar; Boston Erwin Simbolon (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to describe the internal quality assurance process by universities to improve sustainable quality through the one-cycle MSS-PT model, which includes: Setting standards; implementation; monitoring; self-evaluation; internal quality audits; formulation of corrections; and quality improvement. The study results found that the SPMI AKBID Repsati Sumedang cycle consisted of seven steps or stages: Standard Setting, Implementation, Monitoring, SelfEval uation, Internal Quality Audit, Formulation of Corrections, and Quality Improvement for stakeholder satisfaction. In conclusion, the implementation of the SPMI in AKBID Respati Sumedang is carried out by preparing the SPMI design, which is operationally called the SPMI AKBID Respati Sumedang cycle, which is carried out following one year Keyword: SPMI, SPMI implementation, quality assurance process,